Implementation of polyethylene glycol (PEG) as phase change materials in ZNR/P3HT/CUO: PEG inverted organic thin film for solar cell application / Rohanieza Abdul Rahman - Abdul Rahman, Rohanieza (2023)
Solar cell device is considered the most likely candidate as a renewable energy resource that does not emit carbon dioxide, unlike burning fossil fuels. The ability of solar cells to provide and being alternate device in providing the electricity made a striking demand over the years. However, there are few issues in solar cell that need to be considered and solved. One of the common issues in solar cell is its efficiency. The efficiency issue is crucial to be solved because the performance of solar cell is determined by their efficiency. Operating temperature is one of the factor that will affect the performance of solar cells. High operating temperature will drop the efficiency of the solar cells. Also, the configuration and structure of organic solar cell deposited with suitable method also plays an important role in determining the efficiency. The structure and arrangement of the p-n junction must be at optimized condition, to ensure the organic cells gave better performance. To improve the performance, phase change material (PCM) was corporated to the organic solar cell in this study, as the purpose to reduce the operating temperature.